Performance evaluation of oscillating flow regenerators filled with particles, wire screens and high porosity open-cell foams. (5th February 2017) - Peng, Wenping; Xu, Min; Huai, Xiulan; Liu, Zhigang; Lü, Xiaoshu
Highlights: Flow and heat exchange processes of oscillating flow regenerators are simulated. Structural properties of particles, wire screens and foams are compared in detail. A comprehensive performance factor is proposed for the regenerators' evaluation. Performances of regenerators with different porous matrixes are evaluated. High porosity foams are the optimal choice for oscillating flow regenerators. Abstract: The porous matrix filled in oscillating flow regenerators has a significant influence on the performance of the regenerators. In this study, we firstly simulated the heat exchange process of the oscillating flow regenerators with particles, wire screens and high porosity open-cell foams with water as the working fluid using a generalized one-dimensional two-phase thermal-hydraulic model. Then, a detailed evaluation on the performance of these three types of regenerators was carried out regarding unit volume weight, regenerator effectiveness, specific pumping power and the proposed comprehensive performance factor by us as evaluation criteria. The comprehensive performance factor proposed by us is suitable for the performance evaluation and optimizing design of the oscillating flow regenerators because it not only considers the heat exchange ability of the thermal energy by introducing the entransy, but also solves the mismatching between the thermal energy and the pumping power in quality by division operation instead of weighted average algorithm. The evaluating results indicate that high porosity open-cell foams are the optimal choice for the porous matrix used to oscillating flow regenerators from multiple perspectives. The greatest advantage of foams is their high porosity and low pressure drop compared to the other porous structures. This study could also provide a guideline for the other fields involving the porous matrix.